Предмет: Алгебра,
автор: loloshovich83
Упростить выражение.
Приложения:
Ответы
Автор ответа:
0
a-5/a^2+3a - a+5/a^2-3a
Автор ответа:
0
(a-3)(a-5)-(a+5)(a+3)/a(a-3)(a+3)=(a2-5a-3a+15)-(a2+3a+5a+15)/a(a-3)(a+3)=
a2-5a-3a+15-a2-3a-5a-15/a(a-3)(a+3)= -16/a(a-3)(a+3)
a2-5a-3a+15-a2-3a-5a-15/a(a-3)(a+3)= -16/a(a-3)(a+3)
Похожие вопросы
Предмет: Английский язык,
автор: bandanaMAKUSA
Предмет: Математика,
автор: zyonghh
Предмет: Физика,
автор: uajnmorahahaha
Предмет: Математика,
автор: efimovcostia
Предмет: Литература,
автор: Мухаммад20101